Effect of Employee Participation on Organizational Performance with Organizational Commitment as a Moderator - Butali, Peter; Njoroge, David (International Journal of Scientific Research and Management (IJSRM), 2018)
The purpose of this study was to find out the impact of employee participation on organizational performance and to find out the moderating effect of organizational commitment on the relationship between employee participation and organizational performance. The study population comprised of 5866 employees of three state corporations namely Mumias Sugar Company, Kenya Power and KenGen. The study adopted descriptive survey research design. The findings of the study were that employee participation had a significant effect on organizational performance. The study further showed that affective commitment, continuance commitment and normative commitment moderated the relationship between employee participation and organizational performance.